Dystonia rating scales: Critique and recommendations. Issue 7 (25th July 2013) - Albanese, Alberto; Sorbo, Francesca Del; Comella, Cynthia; Jinnah, H. A.; Mink, Jonathan W.; Post, Bart; Vidailhet, Marie; Volkmann, Jens; Warner, Thomas T.; Leentjens, Albert F.G.; Martinez‐Martin, Pablo; Stebbins, Glenn T.; et al.
ABSTRACT Many rating scales have been applied to the evaluation of dystonia, but only few have been assessed for clinimetric properties. The Movement Disorders Society commissioned this task force to critique existing dystonia rating scales and place them in the clinical and clinimetric context. A systematic literature review was conducted to identify rating scales that have either been validated or used in dystonia. Thirty‐six potential scales were identified. Eight were excluded because they did not meet review criteria, leaving 28 scales that were critiqued and rated by the task force. Seven scales were found to meet criteria to be "recommended": the Blepharospasm Disability Index is recommended for rating blepharospasm; the Cervical Dystonia Impact Scale and the Toronto Western Spasmodic Torticollis Rating Scale for rating cervical dystonia; the Craniocervical Dystonia Questionnaire for blepharospasm and cervical dystonia; the Voice Handicap Index (VHI) and the Vocal Performance Questionnaire (VPQ) for laryngeal dystonia; and the Fahn‐Marsden Dystonia Rating Scale for rating generalized dystonia. Two "recommended" scales (VHI and VPQ) are generic scales validated on few patients with laryngeal dystonia, whereas the others are disease‐specific scales. Twelve scales met criteria for "suggested" and 7 scales met criteria for "listed." All the scales are individually reviewed in the online information. The task force recommends 5 specific dystonia scales and suggests to further validate 2 recommended generic voice‐disorder scales in dystonia. Existing scales for oromandibular, arm, and task‐specific dystonia should be refined and fully assessed. Scales should be developed for body regions for which no scales are available, such as lower limbs and trunk. © 2013 Movement Disorder Society